Food insecurity associated with self-reported mental health outcomes in Peruvian households during the COVID-19 pandemic - Anampa-Canales, Maria M.; Huancahuire-Vega, Salomón; Newball-Noriega, Edda E.; Morales-García, Wilter C.; Galvez, Cesar Augusto (Frontiers in Nutrition, 2022)
Background: The global pandemic of COVID-19 and the social distancing efforts implemented worldwide to limit its spread have disrupted the economy, increased food insecurity, and mental health problems. Objectives: The aim of this study was to determine the association between food insecurity and mental health outcomes (stress, depression and anxiety) in Peruvian households during the COVID-19 pandemic. Methods: A cross-sectional investigation was conducted with 525 participants of both sexes (68% women), over 18 years of age and from the three geographic regions of Peru: Coast (54.9%), Highlands (28.4%) and Jungle (16.8%). The data were collected during the year 2021, between July 6 and September 22 through a self-administered online survey designed to assess socio-demographic, socioeconomic, food insecurity and mental health outcomes (depression, anxiety and stress). Results: The majority of households (71.4%) experienced some degree of food insecurity. Mild food insecurity was the most frequent, affecting 49.1%, followed by moderate 15.4% and severe 6.9%. Regarding mental health outcomes, 24.8% manifested depression, 26.7% anxiety and 15.3% stress. With respect to the association between the level of food insecurity and anxiety, this was highly significant (p<0.01). Households with mild, moderate and severe food insecurity are 2.04, 4.5 and 10.44 times, respectively, more likely to have moderate-severe anxiety. On the other hand, the mild food insecurity was not associated with moderate-severe depression. In contrast, households with moderate and severe food insecurity are 2.8 and 5.7 times, respectively, more likely to have moderate-severe depression. Finally, households with moderate food insecurity are 5.9 times more likely to have moderate-severe stress, and households with severe food insecurity are 8.5 times more likely to have moderate-severe stress, both having a highly significant association (p< 0.01). Conclusion: In conclusion, during the second wave of the COVID-19 pandemic in Peru, household food insecurity was independently associated with worse mental health outcomes. Monitoring of both food insecurity and mental health will be important as the COVID-19 pandemic continues.